MODELING RESIDUAL STRENGTH OF PALM KERNEL SHELL CONCRETE USING THE ULTRASONIC PULSE VELOCITY FOR RIGID PAVEMENT MAINTENANCE (Malaysian Journal of Civil Engineering, 2018)
This paper reports the Ultrasonic Pulse Velocity (UPV) test method as a strategy for monitoring the flexural strength of palm kernel shell (PKS) concrete and adoption for routine maintenance of rigid pavements. The direct and indirect UPV measurements were made alongside respective mechanical properties of compression (cube) and flexural (slab) elements of concrete at various mixes and water/cement ratios. A total of 420 cubes (150 mm size) and 28 slabs of the PKS concrete were casted for nominal mixes of 1:1:1, 1:1:2, 1:11/2:3 and 1:2:4 and varying water/cement (w/c) ratios of 0.3-0.7(0.1). The two forms of the structural test elements were cured in water at laboratory temperature for 3, 7, 14, 21, 28, 56 and 91 days. The elements were then subjected to nondestructive testing using the Pundit apparatus for determination of direct ultrasonic wave velocity and the elastic modulus at the various ages. The cubes were subsequently subjected to destructive compressive test. The established velocity-strength data set was then employed for the development of statistical Compressive strength-UPV and strength– Age relationship for the palm kernel shell concrete. Also the indirect UPV measurements were made on the PKS concrete slabs and correlated with the direct UPV. The corresponding flexural strength model at w/c ratio of 0.5 was formulated, and its use as both the quality assurance model and routine rigid pavement maintenance for a lightweight concrete was equally developed. Results show that the UPV and the compressive strength of PKS Concrete increased with age but decreased with increase in w/c ratio and mixes. The strength-UPV models developed for all mixes were in the form of logarithm equation, at R2 values of 90% and more. The application of the developed model for a slab as rigid pavement maintenance/deterioration planning and design was substantially demonstrated in the paper.